Microbiota fúngica de queijo de coalho comercializadas no estado de Alagoas - Ferreira Junior, Genildo Cavalcante (2012)
The presence of fungi in foods one can pose a potential risk to human health because it indicates inadequate sanitary conditions, and can introduce toxic metabolites called mycotoxins. Milk is a food rich in proteins, lipids, minerals and vitamins, among other nutrients. Accordingly, it is an excellent substrate which favors growth of opportunistic pathogenic fungi. The great potential of this food is the cause of various derivatives, among which, the cheese curd, butter, cottage cheese and other products. Based on the above, this study aimed to characterize the pathogenic microflora epiphyte in farmhouse cheese sold in Alagoas. This study was conducted at the Federal University of Alagoas - UFAL, between the months of April 2011 to October 2011. The experimental design was completely randomized. We collected 20 samples of cheese curd from 5 different brands, hypermarkets located in the city of Maceio - AL. Microbiological analyzes were performed in duplicate and triplicate physicochemical and variables were analyzed by counting the number of colony forming units of fungi, identification of mycoflora, and determination of moisture and pH. The samples were plated in medium DRBC (Rose Bengal Agar Dichloran Chloramphenicol), using dilutions of 10-1 to 10-5. The plates were incubated at 25 ° C for five days. After this period, the identification of filamentous fungi occurred in an optical microscope. For the genera and species of fungi that can not be identified after the seven days, was carried microcultures. Filamentous fungi identified were isolated seven genres, highlighting the species Aspergillus flavus and Penicillium sp, potentially producing mycotoxins, thereby representing a danger in the samples analyzed. There was also the need to adopt Good Manufacturing Practices, evidenced by high counts of filamentous fungi count 5,0 x 102 to 1,7 x 106. Cheese curds